IDENTIFICATION OF SCIENTIFICALLY CREATIVE YOUNGSTERS ISSUES AND IMPLICATIONS - Singh, Dr. Chhotan (SCHOOL SCIENCE, 2013)
Creativity has been interpreted differently by different researchers. It is a complex concept encompassing a wide spectrum of activities. Now by putting prefix “Scientific” to an already complex concept, a new dimension is added to it. Hence, the problem arises: what is meant by ‘scientific creativity’? Has scientific creativity some specialities of its own which are different from other types of creativity? This problem can be best attacked by looking into the very nature of science and to choose what special factors or components characterise the scientific creativity.